The potential anti-money laundering and counter-terrorism financing risks and implications of virtual currencies on the prevailing South African regulatory and supervisory regime - Brits, Reghard (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.